Changing dynamics and tail risks of aggregate demand and income distribution - Jose Barrales-Ruiz; Ivan Mendieta-Mu\~noz (The University of Utah, Department of Economics, 2024)
This paper examines the changes in the dynamic interactions between aggregate demand and income distribution in the USA. We focus on two periods that capture the relevant characteristics before and after contemporary neoliberal capitalism. We study the interactions between aggregate demand and income distribution in both periods using structural quantile vector autoregression models. This allows us to assess the informational content of the dynamic interactions at all parts of the relevant distributions, including the potential tail risks. The results show evidence of important reductions in the profit-led effect across the whole distribution of aggregate demand during neoliberalism; while profit squeeze dynamics have decreased at most parts of the distribution of income but have increased its downside risk, thus becoming more heterogeneous across the distribution of income. Notwithstanding the underlying transmission mechanisms have remained unaltered across the two periods, our results highlight that the interactions between aggregate demand and income distribution have become a more complex phenomenon to study since the mid-1980s.
Keywords: D33; E11; E12; E32; 330; aggregate demand; income distribution; tail risks; quantile vector autoregression; neoliberalism